Unveiling potential virulence determinants in Vibrio isolates from Anadara tuberculosa through whole genome analyses - Mariana Restrepo-Benavides; Daniela Lozano-Arce; Laura Natalia Gonzalez-Garcia; Felipe Báez-Aguirre; Gabriela Ariza-Aranguren; Daniel Faccini; María Mercedes Zambrano; Pedro Jiménez; Ana Fernández-Bravo; Silvia Restrepo; Marcela Guevara-Suarez (Microbiology Spectrum, 2024)
ABSTRACTThe genus Vibrio includes pathogenic bacteria able to cause disease in humans and aquatic organisms, leading to disease outbreaks and significant economic losses in the fishery industry. Despite much work on Vibrio in several marine organisms, no specific studies have been conducted on Anadara tuberculosa. This is a commercially important bivalve species, known as “piangua hembra,” along Colombia’s Pacific coast. Therefore, this study aimed to identify and characterize the genomes of Vibrio isolates obtained from A. tuberculosa. Bacterial isolates were obtained from 14 A. tuberculosa specimens collected from two locations along the Colombian Pacific coast, of which 17 strains were identified as Vibrio: V. parahaemolyticus (n = 12), V. alginolyticus (n = 3), V. fluvialis (n = 1), and V. natriegens (n = 1). Whole genome sequence of these isolates was done using Oxford Nanopore Technologies (ONT). The analysis revealed the presence of genes conferring resistance to β-lactams, tetracyclines, chloramphenicol, and macrolides, indicating potential resistance to these antimicrobial agents. Genes associated with virulence were also found, suggesting the potential pathogenicity of these Vibrio isolates, as well as genes for Type III Secretion Systems (T3SS) and Type VI Secretion Systems (T6SS), which play crucial roles in delivering virulence factors and in interbacterial competition. This study represents the first genomic analysis of bacteria within A. tuberculosa, shedding light on Vibrio genetic factors and contributing to a comprehensive understanding of the pathogenic potential of these Vibrio isolates.IMPORTANCEThis study presents the first comprehensive report on the whole genome analysis of Vibrio isolates obtained from Anadara tuberculosa, a bivalve species of great significance for social and economic matters on the Pacific coast of Colombia. Research findings have significant implications for the field, as they provide crucial information on the genetic factors and possible pathogenicity of Vibrio isolates associated with A. tuberculosa. The identification of antimicrobial resistance genes and virulence factors within these isolates emphasizes the potential risks they pose to both human and animal health. Furthermore, the presence of genes associated with Type III and Type VI Secretion Systems suggests their critical role in virulence and interbacterial competition. Understanding the genetic factors that contribute to Vibrio bacterial virulence and survival strategies within their ecological niche is of utmost importance for the effective prevention and management of diseases in aquaculture practices.